БАҲС-МУНОЗАРАНИНГ ЎҚУВЧИ КАМОЛОТИДА ТУТГАН ЎРНИ - Алланазарова, Ш.А. (SCIENCE and SOCIETY, 2018)
The article is devoted to the issues of pedagogical peculiarities of organizing discussions and debates and the role of the teacher in this process.
Keywords: debate; mutual relations; the norms of spirituality and morality; process of discussion; teaching discussion; communication; dialogue; teacher; learner